(untitled) (Bangladesh Journal of Botany, 2021)
Influence of various organic manures with chemical fertilizers on increasing growth, yield and nutritional quality of potato was studied. The experiment consisted of seven treatments including T0: Control, T1: 75% recommended fertilizer dose (RFD); T2: 100% RFD, T3: 75% RFD + Kazi compost (5 t/ha), T4: 75% RFD + Kazi compost (3 t/ha), T5: 75% RFD + Poultry manure (3 t/ha) and T6: 75% RFD + Cowdung (5 t/ha). Among the organic manures, Kazi compost performed the best which compensated up to 25% of recommended inorganic fertilizers and significantly improved the growth components, yield parameters, tuber yield and nutrient uptake by potato. In field performance, Kazi compost @ 5 t/ha was effective followed by poultry manure and can be recommended for better growth, yield and nutritional quality of potato. Bangladesh J. Bot. 50(3): 651-657, 2021 (September)